(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
It is the goal of this study to examine the relationship between consumer satisfaction and various retail business attributes. As everyone know that Indian retail industries are flourishing and Organised retail is chipping away at brick-and-mortar businesses’ market share. According to the findings of previous research, the scale used to assess customer satisfaction includes store atmosphere, shopping convenience, operational competence, service quality, product selection, pricing policy, and services given after the sale. Using a sample of 274 Big Bazaar consumers in West Bengal, India, we tested the suggested model using Smart PLS. According to this study, customers’ satisfaction in the retail business is influenced by a variety of shop factors. Store attributes were shown to be the most significant antecedent of customer satisfaction. By analysing the dimensions of perceived customer satisfaction, this research adds to the understanding the concepts of customer satisfaction. In this study, further research should be done to analyse consumer satisfaction in a variety of retail sectors. A comparison of this idea with other retail categories will be possible. Furthermore, Interrelationship between customer satisfaction components in the retail business must also be studied in details. According to this study, retail managers and executives should aim to influence the atmosphere of their shops as well as the ease of shopping as well as the service quality, product selection, pricing strategy, and after sale services.